Problem : Solve (5+2√6)(x2-3) + (5-2√6)(x2-3) = 10 by using quadratic formula.
Doubt by Muskan
Solution :
Solution :
(5+2√6)(x2-3) + (5-2√6)(x2-3) = 10 ---------(1)
Let y = (5 + 2√6)(x2 - 3)
then 1/y = 1/[(5 + 2√6)(x2 - 3) ]
Let y = (5 + 2√6)(x2 - 3)
then 1/y = 1/[(5 + 2√6)(x2 - 3) ]
1/y = [1/(5+2√6)](x2 - 3)
[On Rationalising the denominator]
1/y = (5 + 2√6)(x2 - 3)
[On Rationalising the denominator]
1/y = (5 + 2√6)(x2 - 3)
On putting these values of y and 1/y in equation in eq (1)
y + 1/y = 10
(y2 + 1)/y = 10
(y2 + 1) = 10y
y2 - 10y + 1 = 0
a = 1
b = -10
c = 1
D = b2 - 4ac
D = (-10)2 - 4(1)(1)
D = 100 - 4
D = 96
Using Quadratic Formula
y = (- b ± √D) / 2a
y = [-(10) ± √96] / 2(1)
y = (10 ± 4√6) / 2
y = 2(5 ± 2√6) / 2
y = 5 ± 2√6
When y = 5 + 2√6
(5 + 2√6)(x2-3) = (5 + 2√6)1
Equating the Power Both Sides
x2 - 3 = 1
x2 = 1 + 3
x2 = 4
x = ± √4
x = ± 2
When y = 5 - 2√6
(5 + 2√6)(x2-3) = 5 - 2√6
(5 + 2√6)(x2-3) = [1/(5 - 2√6)]-1
(5 + 2√6)(x2-3) = (5 + 3√6)-1
[Rationalising the denominator]
Equating the Power Both Sides
x2 - 3 = -1
x2 = -1+3|
x2 = 2
x = ± √2
∴ x = ± 2, ±√2